A malignant lymphoma presenting as a non-healing oral ulcer / Ahmad Izani Mohd Safian ... [et al.] - Mohd Safian, Ahmad Izani; Zulkarnain, Sarah; Hussain, Faezahtul Arbaeyah; Husin, Azlan; Aziz, Azliana; Mohamad, Irfan (Faculty of Medicine, 2022)
Lymphomas are the second most common non-epithelial malignant tumour in the oral and maxillofacial region. Non-Hodgkin lymphoma (NHL) is more frequently diagnosed eventhough oral cavity involvement is less than 4% of all NHLs. Usually, the oral manifestation of NHL is secondary to the widespread involvement. Primary oral NHL is relatively rare and difficult to diagnose in clinical setting as it presents as local swelling, pain, discomfort and mimics pyogenic granuloma, periodontal disease, osteomyelitis and other malignancies. A chronic, solitary non-healing ulcerative lesion of the oral mucosa is often misdiagnosed as nonneoplastic especially in a previously healthy young adult. Here, we share a case of extranodal diffuse large B-cell lymphoma of the soft palate, in a 22-year-old healthy gentleman with no other symptoms. Meticulous clinical evaluation and complete investigations are required for prompt diagnosis, timely treatment which carries better prognosis.